Measurement Of The Level Of Educator Discipline And Preparation Of Teaching Materials On The Quality Of Graduates - Hanik, Kumila; Purnomo, Suwito Eko; Yulianto, Arif; Utomo, Cahyo Budi (Universitas Negeri Semarang, 2024)
A teacher must have competence in both discipline and preparation of teaching materials because a teacher has an obligation to educate the nation's children so that the teaching and learning process can be created well and the quality of graduate students can be achieved well. The objectives of this study are (1) to determine whether teacher discipline partially affects the quality of graduate students at SMK Wisudha Karya Kudus; (2) to find out whether the preparation of teacher teaching materials partially affects the quality of graduate students at SMK Wisudha Karya Kudus; (3) to find out whether teacher discipline and the preparation of teacher teaching materials affect the quality of graduate students at SMK Wisudha Karya Kudus. This research includes field research. Research place at SMK Wisuda Karya Kudus. Data collection methods using Questionnaires, Documentation Sheets, Observation Sheets. The results showed that (1) Teacher discipline partially affected the quality of graduate students at SMK Wisudha Karya Kudus with sufficient categories of 45.6%, while the remaining 54.4% was influenced by other factors that were not studied. (2) The preparation of teacher teaching materials partially affects the quality of graduate students at SMK Wisudha Karya Kudus with sufficient categories of 23.5%, while the remaining 76.5% is influenced by other factors that are not studied. (3) Teacher discipline and preparation of teacher teaching materials simultaneously affect the quality of graduate students at SMK Wisudha Karya Kudus by showing a fairly good category of 52.18%, while the remaining 47.82% is influenced by other factors that are not studied.